2022
DOI: 10.1111/jiec.13319
|View full text |Cite
|
Sign up to set email alerts
|

Sharing economy rebound: The case of peer‐to‐peer sharing of food waste

Abstract: The Sharing Economy is commonly assumed to promote sustainable consumption and improve material efficiency through better utilization of existing product stocks. Yet the cost-savings and convenience of using sharing economy platforms can ultimately stimulate additional demand for products and services. As a result, some or even all of the expected environmental benefits attributed to sharing could be negated, a phenomenon known as Rebound Effect. Relying on a unique dataset covering close to 1.1 million exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 90 publications
(189 reference statements)
0
10
0
Order By: Relevance
“…Some authors question the ability of FWMAs to curb food waste significantly. Mathisen and Johansen (2022) reported no significant impact of FWMAs on the quantity of food waste, and Meshulam et al (2023) find that FWMAs had negative environmental externalities. However, both studies used small samples; expanding them to include more cases and more interviews with participants would make it possible to draw more convincing conclusions.…”
Section: Mobile Applications In Food Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors question the ability of FWMAs to curb food waste significantly. Mathisen and Johansen (2022) reported no significant impact of FWMAs on the quantity of food waste, and Meshulam et al (2023) find that FWMAs had negative environmental externalities. However, both studies used small samples; expanding them to include more cases and more interviews with participants would make it possible to draw more convincing conclusions.…”
Section: Mobile Applications In Food Supply Chainmentioning
confidence: 99%
“…An FWMA called OLIO and data from seven scenarios were used to analyze whether food-sharing behavior would result in higher environmental impact and if there was a rebound effect (Meshulam et al, 2023). The authors found that a portion of the potential environmental benefits could be offset by the rebound effect from sharing.…”
Section: Mobile Applications In Food Supply Chainmentioning
confidence: 99%
“…Second, sharing often saves users money which they then typically re-spend on additional products and services, a phenomenon referred to as respending or indirect rebound effect (Meshulam et al 2023). The rebound effect can occur when platform users save money (by collecting free food for example) and then use these savings to buy other things (Druckman et al 2011, Makov and Font Vivanco 2018, Sorrell et al 2020.…”
Section: Displacement and Rebound Effectsmentioning
confidence: 99%
“…, 2021). Furthermore, although the wide range of positive effects of these platforms has been extensively demonstrated (de Almeida Oroski and da Silva, 2022), some scholars have pointed out that rebound effects could limit the potential to achieve meaningful reductions in environmental burdens through sharing (Meshulam et al. , 2022).…”
Section: Theoretical Background and Research Contextmentioning
confidence: 99%
“…The analysis of the nature and flow of food exchange between users of varying income levels neither indicates that these platforms are able to redistribute food across income categories nor are they a useful solution in mitigating food insecurity (Makov et al, 2020(Makov et al, , 2023Nica-Avram et al, 2021). Furthermore, although the wide range of positive effects of these platforms has been extensively demonstrated (de Almeida Oroski and da Silva, 2022), some scholars have pointed out that rebound effects could limit the potential to achieve meaningful reductions in environmental burdens through sharing (Meshulam et al, 2022).…”
Section: Food Sharing Platforms: State-of-the-art and Open Issuesmentioning
confidence: 99%